Al-Tarbiyah al-Islamiyyah wa Dauruha fi Tarbiyah Syakhsiyah al-Tullab - Rumadani Sagala (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Personality is a compact word, easy to say, but how difficult to realize. Etymologically, the personality comes from the Latin language persona. This word refers to a mask or a mask used by actors in classical drama. Personality is the very nature which is reflected in the attitudes and actions of a person or a nation that sets it unique from people or other nations. In Islamic educational context, personality is as characteristic and also identity of Islam, the religion that since the fall carries out the mandate to enhance the personality and noble character. Personality itself can be judged only when the research has done and met the scientific criteria. There for, the personality can be taught in schools, introduced to the students through habituation, ideals and ethics. In the al-Qur’an frequently mentioned term about the formation and development of the human personality, the factors that influence it and also how to handle it. Muslims and believers from the perspective of Islam are those who always train their heart and not easily angry (patient), tawakkal, generous, obedient to Allah, as well as maintaining the attitude and deed of the tendency of his own lust